Kepemilikan Institusional, Firm Size, Profitabilitas, Leverage, dan Kebijakan Dividen - Siti Nurlaela; Ainun Jamil Meidikna; Riana R Dewi (UNIVERSITAS NUSANTARA PGRI KEDIRI, 2020)
This study aims to examine the effect of institutional ownership, firm size, profitability, and leverage on dividend policy. Population in this study is basic industry and chemicals companies on Indonesia Stock Exchange (IDX) 2012-2018. Sample of this study were 8 companies selected by purposive sampling method. Statistical methods use multiple linear regression analysis. Result of this study show institutional ownership, firm size, and leverage has influence on dividend policy. While, profitability has no influence on dividend policy